Análisis de la caracterización fisicoquímica de los sedimentos producto del dragado en el Puerto de Barranquilla – Atlántico, con fines de interés ambiental y civil. (2024)
Colombia is a country with a strategically important location, as it’s surrounded by seas and rivers, which provides the potential for significant economic development in terms of port growth. It has been observed that various governments, at both the departmental and national levels, have made significant efforts to invest in and encourage the movement of national and international goods through navigation. To achieve this, it is necessary to ensure the navigability of the rivers. The Magdalena River is one of the main rivers affected by sedimentation due to various factors, and significant amounts of money and effort are required to maintain the required depth levels to ensure that operational centers like the Port of Barranquilla can receive and dispatch various types of merchandise. The development of this research arises precisely from concerns about the current management of sediments resulting from these dredging activities. For this purpose, sampling and laboratory analysis of this material were carried out, as well as geoprocessing of bathymetric surveys conducted before and after dredging activities during the year 2021. This analysis aimed to assess potential impacts on human health and the ecosystem, as well as the potential reuse of this material in terms of recycling, using other countries as a reference. Among the results, an analysis of the pollutant load contributed by the final disposal of these residues is presented, as well as the regulatory deficiencies that currently exist in the country regarding these issues. Finally, this research opens the door to the need for more in-depth studies to propose effective actions that CARACTERIZACIÓN SEDIMENTOS DEL DRAGADO EN BARRANQUILLA. 9 contribute to the achievement of the Sustainable Development Goals in Colombia.